A COMPARISON OF THE SPEECH STYLES OF NIGERIAN AND CHINESE EFL LEARNERS IN MALAYSIA - Pauline Mackenzie; Kuang Ching Hei (University of Kuningan, 2015)
This paper focused on the speech styles of two groups of learners, Nigerian learners with English as their official language and Chinese learners with English as a foreign language studying in Malaysia. A questionnaire was developed to extract personal details while a classroom task was given to gather data. Consent was given voluntarily. Spoken data were recorded, transcribed verbatim and then analyzed and findings were further substantiated by an interview. Analysis showed that Nigerian learners are less prone to using fillers as compared to Chinese EFL learners. This implied that Chinese EFL learners were less comfortable in using English. Both Nigerian and Chinese learners used the same amount of intensifiers suggesting that they do not feel passionate when talking about themselves, as the task demanded. The findings of this study will enable foreign language learners to understand themselves better and assist local teachers and classmates to be more tolerant when communicating with them as it can help to minimize misunderstandings. Nonetheless, further research may be required to verify the findings.Keywords: Speech styles, fillers, intensifiers, Nigerian, Chinese, EFL learners